Enhanced oxidation of arsenite to arsenate using tunable K+ concentration in the OMS-2 tunnel - Hou, Jingtao (2019)
Cryptomelane-type octahedral molecular sieve manganese oxide (OMS-2) possesses high redox potential and has attracted much interest in its application for oxidation arsenite (As(III)) species of arsenic to arsenate (As(V)) to decrease arsenic toxicity and promote total arsenic removal. However, coexisting ions such as As(V) and phosphate are ubiquitous and readily bond to manganese oxide surface, consequently passivating surface active sites of manganese oxide and reducing As(III) oxidation. In this study, we present a novel strategy to significantly promote As(III) oxidation activity of OMS-2 by tuning K+ concentration in the tunnel. Batch experimental results reveal that increasing K+ concentration in the tunnel of OMS-2 not only considerably improved As(III) oxidation kinetics rate from 0.027 to 0.102 min−1, but also reduced adverse effect of competitive ion on As(III) oxidation. The origin of K+ concentration effect on As(III) oxidation was investigated through As(V) and phosphate adsorption kinetics, detection of Mn2+ release in solution, surface charge characteristics, and density functional theory (DFT) calculations. Experimental results and theoretical calculations confirm that by increasing K+ concentration in the OMS-2 tunnel not only does it improve arsenic adsorption on K+ doped OMS-2, but also accelerates two electrons transfers from As(III) to each bonded Mn atom on OMS-2 surface, thus considerably improving As(III) oxidation kinetics rate, which is responsible for counteracting the adverse adsorption effects by coexisting ions.